A Comprehensive Examination of the 1852 Persian Military Manual: ‘General Regulations for the Exercises and Marches of the Infantry of the Esteemed Government of Iran’ - Khorasani, Manouchehr Moshtagh (Faces of War, 2024)
This article deals with the study and analysis of an important Persian military manual, entitled ‘General Regulations for the Exercises and Marches of the Infantry of the Esteemed Government of Iran’ ( قواعد کلیه از برای مشق و حرکات پیاده نظام دولت علیه ایران ). The manual, a historical artefact of considerable importance, is dated Ramadan 1268 Hijra, corresponding to June 1852 CE, a period marked by the reign of Nāssereldin Shāh Qajar. The manual is a testament to the modernisation efforts initiated by Crown Prince Abbās Mirzā during the early Qajar era. It provides a unique insight into the military strategies and training methods of the time, reflecting the transformative changes within the Iranian military. Comprising 51 pages and adorned with 35 illustrations, the manual provides a comprehensive guide to training exercises for armed and unarmed infantry troops. It provides insight into the rigorous training regimes and tactical manoeuvres of the Persian infantry in the mid-19th century. Thus, the manual is not merely a military guide but a historical document that provides information on the evolution of Persian military tactics in response to the modernisation efforts of the time.